Podapolipid mites (Acari: Heterostigmata): key to genera, biogeographical history and description of four new Australian species of Eutarsopolipus - Seeman, Owen D.; Katlav, Alihan (Zootaxa, 2024)
Four new species of parasitic mites of the genus Eutarsopolipus (Trombidiformes: Podapolipidae) are described from Australian carabid beetles: E. ampullaceous sp. nov. (ochoai species group) from Lecanomerus niger (Harpalini); E. tripodus sp. nov. (ochoai species group) from Notolestus sulcipennis (Pterostichini); E. vepreculus sp. nov. (leytei species group) from Coleolissus papua (Harpalini); and E. walteri sp. nov. (myzus species group) from Chlaenius ophonoides (Chlaeniini). Keys to the world genera of Podapolipidae and to the Australian species of Eutarsopolipus are provided. We further reviewed the world distribution of Eutarsopolipus species groups and postulated that the Australian representatives could be classified into two distinct faunas: a putatively Gondwanan fauna represented mainly by the ochoai species group and a more recent Laurasian fauna represented by just a few species in the myzus and acanthomus species groups.